2017
DOI: 10.3389/fmicb.2017.02387
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of the Microbial Community Composition with a Focus on Toxic Cyanobacteria and Toxin Presence during Harmful Algal Blooms in Two South German Lakes

Abstract: Bacterioplankton plays an essential role in aquatic ecosystems, and cyanobacteria are an influential part of the microbiome in many water bodies. In freshwaters used for recreational activities or drinking water, toxic cyanobacteria cause concerns due to the risk of intoxication with cyanotoxins, such as microcystins. In this study, we aimed to unmask relationships between toxicity, cyanobacterial community composition, and environmental factors. At the same time, we assessed the correlation of a genetic marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 86 publications
(124 reference statements)
1
33
1
Order By: Relevance
“…AF-1 supernatant [11]. Many research studies have shown that there was a positive correlation between microcystin production and cyB abundance [66][67][68][69]. Sp34 demonstrated an obvious advantage in the greater inhibition extent of microcystin synthesis-related gene transcription over the reported algicidal bacteria and compounds.…”
Section: Discussionmentioning
confidence: 99%
“…AF-1 supernatant [11]. Many research studies have shown that there was a positive correlation between microcystin production and cyB abundance [66][67][68][69]. Sp34 demonstrated an obvious advantage in the greater inhibition extent of microcystin synthesis-related gene transcription over the reported algicidal bacteria and compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Massive literatures reveal that most algal bloom studies have focused on lakes [ 5 , 6 , 7 ] and oceans [ 8 ]. Characterization of bacterial communities associated with algal blooms in eutrophic lakes from the United States [ 5 ], Norway [ 6 ], Germany [ 7 ] and China [ 8 ], investigated using the 16S rRNA gene sequence method, have demonstrated that algal blooms are a biological disturbance to lake bacterial communities. However, Scherer et al [ 7 ] recently examined the dynamics of the water microbial community associated with cyanobacteria blooms in two recreational lakes in southern Germany and found that bloom toxicity could influence but did not change the bacterial community composition.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, researchers have focused on the geographical distribution of microorganisms in oceans and temperate lakes, but relatively few studies have been done on urban lakes [8,9]. In recent years, the eutrophication of urban lakes, especially the outbreak of algae, is a potential huge hazard to people's lives due to its special geographical location and can seriously affect the development and utilization of water resources [10]. Thus, studies on the fundamental features of urban lake ecosystems are of great importance because they can provide a theoretical basis for our better recovery and management of urban lakes.…”
Section: Introductionmentioning
confidence: 99%